Evolution of the principles of area protection of the urban landscape in Polish planning activities - Tomczak, Anna Aneta (Przestrzenny wymiar badań dziedzictwa kulturowego: Studia z Geografii Politycznej i Historycznej 2020. T. 9-10, 2021)
This chapter presents the most important stages in creating the principles of area protection in urban development documents. The creation of legal grounds and applied practices started from the moment Poland regained its independence, i.e. from the beginning of the interwar period, characterised by an intensification of efforts to formally sanction the protection of national heritage. In the post-war period, historical and urban studies were important, documenting the stages of development of settlement units and placing a value on their cultural worth. A breakthrough in the protection of the historic structure of cities occurred in the 1960s and 1970s, when area-based conservation zones and the principles of creating development guidelines for formal planning documents were introduced in urban planning practice. The area-based approach is also present in contemporary urban development directions and in the rules for the preparation of local zoning plans and revitalisation plans.